EU Legal Framework for Safeguarding Air Passenger Rights - Rossi Dal Pozzo, Francesco (Springer, 2016)
This book presents a thorough analysis of the EU provisions and legal framework of passenger rights in the civil aviation field. It provides both a theoretical and practical view of the initiatives that have been taken in this field. This includes initiatives taken by the European Commission (EC) with the aim to improve the protection of passengers and by the European Court of Justice (ECJ) with regard to jurisprudence. The book points out the goals that have been obtained so far, as well as the goals that still need to be pursued. Particular attention is paid to EU institutions that have been created ad hoc to supervise aviation safety and harmonize the various safety procedures of the EU Member States. Recent and upcoming packages of important safety and security measures are examined in detail. The book gives examples of current applications of legislative instruments and presents readers with the tools to gain a deeper understanding of the legal, practical and theoretical aspects of this important topic in aviation.